2013
DOI: 10.1128/jvi.01798-13
|View full text |Cite
|
Sign up to set email alerts
|

Recombination-Dependent Oligomerization of Human Papillomavirus Genomes upon Transient DNA Replication

Abstract: We describe the extensive and progressive oligomerization of human papillomavirus (HPV) genomes after transfection into the U2OS cell line. The HPV genomic oligomers are extrachromosomal concatemeric molecules containing the viral genome in a head-to-tail orientation. The process of oligomerization does not depend on the topology of the input DNA, and it does not require any other viral factors besides replication proteins E1 and E2. We provide evidence that oligomerization of the HPV18 and HPV11 genomes invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 79 publications
2
50
0
Order By: Relevance
“…1A. With D/H-digested DNA, a pattern of migration was observed for HPV18 sequences that was consistent with open circular and supercoiled forms of episomal DNA (48). Digestion with EcoRI resulted in all hybridizing species migrating at the position of the ϳ8-kb linearized nonintegrated HPV genome as the linearized pBluescript-HPV18 plasmid digested with EcoRI (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…1A. With D/H-digested DNA, a pattern of migration was observed for HPV18 sequences that was consistent with open circular and supercoiled forms of episomal DNA (48). Digestion with EcoRI resulted in all hybridizing species migrating at the position of the ϳ8-kb linearized nonintegrated HPV genome as the linearized pBluescript-HPV18 plasmid digested with EcoRI (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, following several challenges to the prevailing view of slow dsDNA virus evolution (where mechanisms such as recombination are possible [57][58][59][60][61]), there is a need for more direct investigations into the evolutionary potential of HPV variants.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators working with HPV-positive cancer cell lines initially believed that viral genomes in these cells only existed in an integrated form, though Choo et al (1989) discovered episomes as interlocking rings of HPV16 dimers. In transfected U2OS and C33A cells, HPV-positive SiHa and HeLa cells, and cervical and oropharyngeal tumors, Orav et al (2013) also found catenated (chain-linked) multimeric episomes. A recent study of cervical cancer samples reported a range of PV genome presentations, from one integrated copy to integrated tandem repeats to coexisting integrated and episomal forms.…”
Section: Differentiation and Integrationmentioning
confidence: 92%
“…For instance, in ID13 cells, a C127-derived cell line, BPV genomes were found not only as monomeric and oligomeric episomes but were also found in tandem repeats integrated within host chromosomes (Schvartzman et al 1990). Even though PV genomes are typically maintained as monomeric, multi-copy episomes, some studies have reported the presence of multimeric episomes both in cell culture and in samples from infected patients (Kennedy et al 1987, Choo et al 1989, Kristiansen et al 1994, Orav et al 2013.…”
Section: Maintenancementioning
confidence: 98%
See 1 more Smart Citation